The Development of a Quantitative RCM/MSG Application using Microsoft Office - R Sianturi; E Suwondo (Institut Teknologi Bandung, 2020)
The number of small to medium scale industries makes the development of a low cost and easy to use application to support maintenance programs development is necessary. Besides for industries, the developed application can be used also in the academic field for research. For cost reasons, the application is developed using Microsoft Access and Microsoft Excel. The development of the application is carried out in three steps, i.e. the determination of application specifications, the programming in Microsoft Access and Microsoft Excel, and the validation and user-friendly test. The application is developed by considering the relationship between the risk quantification of a failure effect and the selection of a maintenance task and its interval. The effectiveness assessments are based on the failure risk reduction up to an acceptable level. The developed application is named